Reader Rabbit. Toddler (CD.ROM) - Learning Company (Novato, CA Learning Co)
Reader Rabbit and Mat the Mouse introduce letters, numbers, colors, shapes and vocabulary
Title from disc label
4
Keywords: CD.ROM (Children ); Education, Preschool; Juvenile software